2010
DOI: 10.1590/s0104-11692010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Nursing communication in nursing care to mastectomized women: a grounded theory study

Abstract: The goal was to understand the nurse / patient communication process, emphasizing nursing care to mastectomized women. Symbolic Interactionism and Grounded Theory were used to interview eight nurses from a referral institution in cancer treatment, using the guiding Interacionismo Simbólico e a Grounded Theory, para entrevistar oito enfermeiras de uma instituição de referência no tratamento do câncer, utilizando a questão norteadora: como a enfermeira percebe seu processo de comunicação com a mulher mastectomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The differences between theoretical and practical information, which harm the implementation of the nursing process, are indicated (11) . The need to seek strategies to minimize this gap is highlighted in order to implement the continuous development of the work process, taking the challenge of a critical and reflexive paradigm (12) , in which, even in the face of limitations in the communicative process, nurses show possibilities for changes emphasizing professional education and qualification (13) . It implies that professionals should have an interest and responsibility in the face of routine situations as reinforced in a study addressing the preparedness of nurses to deliver care (14) .…”
Section: Introductionmentioning
confidence: 99%
“…The differences between theoretical and practical information, which harm the implementation of the nursing process, are indicated (11) . The need to seek strategies to minimize this gap is highlighted in order to implement the continuous development of the work process, taking the challenge of a critical and reflexive paradigm (12) , in which, even in the face of limitations in the communicative process, nurses show possibilities for changes emphasizing professional education and qualification (13) . It implies that professionals should have an interest and responsibility in the face of routine situations as reinforced in a study addressing the preparedness of nurses to deliver care (14) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to reach a satisfactory and humanized communication the nurse must involve herself and believe that her presence is very important concerning the performers of technical procedures [7], once not always the technical knowledge does not work so well facing situations of stress such as the subjective knowledge reviewed in the communication. Standing beside the patient to listen to him is a therapy action which should be recognized [8].…”
Section: Discussionmentioning
confidence: 99%
“…One study of Koinberg, Holmberg & Fridlund [39] showed that patient satisfaction with the knowledgeable and professional skills of the nurses was high. Another study IMA et al [40] identified acceptance and valuation by the clientele of nurses' clinically based conversations. With respect to developing an understanding of nursing from the perspective of caring in nursing from the perspective of cancer patients through 20 interviews Liu, Mok & Wong, [41] the findings showed that caring in nursing as perceived by cancer patients involves nurses having qualified professional knowledge, attitudes and skills in oncology and providing the informational, emotional and practical support and help required by cancer patients.…”
Section: Conversation Gives Support To Cancer Patientsmentioning
confidence: 99%